Perception of Game-Based Rehabilitation in Upper Limb Prosthetic Training: Survey of Users and Researchers - Garske, Christian Alexander; Dyson, Matthew; Dupan, Sigrid; Nazarpour, Kianoush (JMIR Publications, 2021)
BackgroundSerious games have been investigated for their use in multiple forms of rehabilitation for decades. The rising trend to use games for physical fitness in more recent years has also provided more options and garnered more interest for their use in physical rehabilitation and motor learning. In this study, we report the results of an opinion survey of serious games in upper limb prosthetic training. ObjectiveThis study investigates and contrasts the expectations and preferences for game-based prosthetic rehabilitation of people with limb difference and researchers. MethodsBoth participant groups answered open and closed questions as well as a questionnaire to assess their user types. The distribution of the user types was compared with a Pearson chi-square test against a sample population. The data were analyzed using the thematic framework method; answers fell within the themes of usability, training, and game design. Researchers shared their views on current challenges and what could be done to tackle these. ResultsA total of 14 people with limb difference and 12 researchers participated in this survey. The open questions resulted in an overview of the different views on prosthetic training games between the groups. The user types of people with limb difference and researchers were both significantly different from the sample population, with χ25=12.3 and χ25=26.5, respectively. ConclusionsWe found that the respondents not only showed a general willingness and tentative optimism toward the topic but also acknowledged hurdles limiting the adoption of these games by both clinics and users. The results indicate a noteworthy difference between researchers and people with limb difference in their game preferences, which could lead to design choices that do not represent the target audience. Furthermore, focus on long-term in-home experiments is expected to shed more light on the validity of games in upper limb prosthetic rehabilitation.